Staff Appraisal and Performance of Commercial Banks in Uganda: A Case Study of Centenary Bank, Kabale Branch. - Twasima, Claire (Kabale University, 2023)
The study was about examining the appraisal of staff and the performance of Commercial Banks in Uganda, using the case of Centenary Bank, Kabale Branch. Chapter One provided the necessary background, statement of the problem, purpose of the study, objectives of the study, research questions, significance of the study area, and scope of the study. Chapter two covered a written discussion of the related literature search. The study reflected the objectives of the research about the impact of bookkeeping practices on the performance of small business enterprises in Kabale Municipality. While reviewing, the research mainly focused on Appraising staff which was the independent variable whereas performance was the dependent variable. Under the independent variable (Appraising staff) the study focused on, Performance standards, and discussing results with employees (feedback). While the dependent variable (performance) focused on customer satisfaction, accountability, efficiency, and effectiveness. Chapter three dealt with the methods. and tools the researcher used in data collection and analysis. It described the research design that was used by the researcher, data sources and collection tools, processing, analysis, and the challenges that the researcher faced. Chapter four focused on the analysis and report of the results of the study. The main issues covered are the demographics of the respondents and data presentation in terms of tables and charts to address the objectives of the study. Chapter five provides a discussion of the findings from chapter four, and it also gives the conclusions and recommendations of the study based on the objective of the study.